Principal environmental impacts on pipeline tracks as a result of mining operations and their mitigated actions - Ferreira, Gilda Carneiro [UNESP]; Chang, Maria Rita Caetano [UNESP]; Lemos, Cássia Maria Gama (FapUNIFESP (SciELO), 2016)
This study deals with the main environmental impacts and possible mitigation measures for many pipeline tracks, due to the mining of different substances in areas of interference between mining activities and mineral research and those resulting from construction and gas pipeline operation. By monitoring the identified interferences/ disturbances, it was determined that although punctual and small in number, the extraction of mineral resources in the proximity of the gas pipelines could represent risks for the security of the undertaking. In general the risks are consequence either of the use of explosives or of induced erosive processes that could lead to pipeline instability. It is necessary to block the mining activities on both sides of the pipeline tracks in order to minimize risks to the pipeline, to others, to society, and to the environment. Also, the establishment of “flexible” track limits could be adopted in areas adjacent to the pipelines for the exploration of some mineral deposits, thus prioritizing security preservation with a minimum of socio-environmental impacts.
Keywords: Environmental disturbance; Gas pipeline; Mineral extraction